ULTRASONIC METHODS OF ANALYSIS OF THE METAL ARTICLES SURFACE HARDENING - A. R Baev; A. I. Majorov; M. A. Tishchenko (Литьë и металлургия, 2010)
The results of investigation of the way and device for measuring with nondestructive method of hardened case thickness are described. The data of measurements do not depend on the steel grade.